The identification of new roles for nicotinamide mononucleotide after spinal cord injury in mice: an RNA-seq and global gene expression study - Zhang, Chunjia; Li, Yan; Bai, Fan; Talifu, Zuliyaer; Ke, Han; Xu, Xin; Li, Zehui; Liu, Wubo; Pan, Yunzhu; Gao, Feng; Yang, Degang; Wang, Xiaoxin; et al. (Frontiers in Cellular Neuroscience, 2023)
Background Nicotinamide mononucleotide (NMN), an important transforming precursor of nicotinamide adenine dinucleotide (NAD+). Numerous studies have confirmed the neuroprotective effects of NMN in nervous system diseases. However, its role in spinal cord injury (SCI) and the molecular mechanisms involved have yet to be fully elucidated. Methods We established a moderate-to-severe model of SCI by contusion (70 kdyn) using a spinal cord impactor. The drug was administered immediately after surgery, and mice were intraperitoneally injected with either NMN (500 mg NMN/kg body weight per day) or an equivalent volume of saline for seven days. The central area of the spinal cord was harvested seven days after injury for the systematic analysis of global gene expression by RNA Sequencing (RNA-seq) and finally validated using qRT-PCR. Results NMN supplementation restored NAD+ levels after SCI, promoted motor function recovery, and alleviated pain. This could potentially be associated with alterations in NAD+ dependent enzyme levels. RNA sequencing (RNA-seq) revealed that NMN can inhibit inflammation and potentially regulate signaling pathways, including interleukin-17 (IL-17), tumor necrosis factor (TNF), toll-like receptor, nod-like receptor, and chemokine signaling pathways. In addition, the construction of a protein-protein interaction (PPI) network and the screening of core genes showed that interleukin 1β (IL-1β), interferon regulatory factor 7 (IRF 7), C-X-C motif chemokine ligand 10 (Cxcl10), and other inflammationrelated factors, changed significantly after NMN treatment. qRT-PCR confirmed the inhibitory effect of NMN on inflammatory factors (IL-1β, TNF-α, IL-17A, IRF7) and chemokines (chemokine ligand 3, Cxcl10) in mice following SCI. Conclusion The reduction of NAD+ levels after SCI can be compensated by NMN supplementation, which can significantly restore motor function and relieve pain in a mouse model. RNA-seq and qRT-PCR systematically revealed that NMN affected inflammation-related signaling pathways, including the IL-17, TNF, Toll-like receptor, NOD-like receptor and chemokine signaling pathways, by down-regulating the expression of inflammatory factors and chemokines.